Comparative Analysis of Patient Satisfaction and Sedation Outcomes in Bronchoscopy: Fentanyl/Chlorpheniramine vs. Ketamine/Chlorpheniramine - Mohammadreza Khajavi; Leila Sadat Hosseini; Marzieh Pazoki; Seyed Hamidreza Sharifnia; Reza Shariat Moharari; Pejman Pourfakhr; Parisa Kianpour; Abbas Ostadalipour; Atabak Najafi; Farhad Etezadi (Acta Medica Iranica, 2024)
This randomized clinical trial aimed to assess and compare patient satisfaction and sedation outcomes in bronchoscopy procedures using two distinct sedation protocols: fentanyl/chlorpheniramine (FC) and ketamine/chlorpheniramine (KC). Ninety patients undergoing simple bronchoscopy and bronchoalveolar lavage were randomly assigned to receive either FC (1 µg/kg fentanyl and 10 mg chlorpheniramine) or KC (0.5 mg/kg ketamine and 10 mg chlorpheniramine). Lidocaine was also administered during bronchoscopy. Primary outcomes included patient satisfaction scores, while secondary outcomes encompassed sedation levels, bronchoscopist satisfaction, cough rates, lidocaine usage, and physiological parameters. Patients in the FC group exhibited significantly higher satisfaction levels compared to the KC group (P=0.002). Bronchoscopist satisfaction was also superior in the FC group (P=0.001). Although cough rates did not differ significantly, severe persistent coughs were more prevalent in the KC group. Physiological parameters such as oxygen saturation were comparable, but the KC group demonstrated higher increases in systolic blood pressure and heart rate. The use of fentanyl/chlorpheniramine resulted in higher patient and bronchoscopist satisfaction during simple bronchoscopy and bronchoalveolar lavage compared to ketamine/chlorpheniramine. This study suggests that the combination of fentanyl and chlorpheniramine may be a preferable sedation choice for bronchoscopy procedures.